PENERAPAN RANCANGAN SISTEM INFORMASI AKUNTANSI SIKLUS PRODUKSI (MENGHITUNG HPP MAKANAN) DENGAN MENGUNAKAN ACCURATE ACCOUTING SYSTEM PADA INDUSTRI MAKANAN RESTO XYZ - Safri Safri (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACTGood business in the administration section is a business that can present reports quickly and accurately. Financial statements can be presented when needed, because financial statements are information that can be managed by management. In accordance with the era, digitalization is needed in business processes. In the XYZ Resto food business, where companies process raw materials into products that are ready to sell, of course the business model is an industrial business, but in its application there are obstacles, where the Accurate Enterprise module is too broad for companies with an urgent implementation time, and operational do not need the model. By engineering defauld of the system, the use of accurate accounting system can be applied. There are advantages of applying the Cost of Production in Resto XYZ, where the defauld can adjust to what is needed by the company, where the trial and error results of the Financial Statements presented can satisfy the needs of management, besides that users as field executors also feel no hassle. There are also weaknesses in its application, where the strength of the inventory cannot be presented, but it is in accordance with the wishes of management. Keywords: Accurate Enterprise, Cost of Production